2020
DOI: 10.1155/2020/8024598
|View full text |Cite
|
Sign up to set email alerts
|

Salvage after Retroperitoneal Kidney Allograft Torsion

Abstract: Torsion of a transplanted kidney into the retroperitoneal space is a rare occurrence, with only three other reported cases. Failure after kidney transplantation is caused by surgical, immunological, and infective complications. Torsion is a complication that poses a serious risk of ischemic graft failure, and, if suspected, sonographic evaluation helps ascertain the diagnosis. Here, we present the case of a 69-year-old transplant recipient whose routine postoperative ultrasound confirmed vessel patency, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, torsion has been a rare complication for kidneys transplanted into the retroperitoneal space. 32,33 Torsion associated with RAKAT has been accounted for by the intraperitoneal placement of the transplanted kidney, and the argument has been made that the retroperitoneal space should be the preferred location of the transplanted kidney. 17 Lastly, Kaouk et al reported that no postoperative complications were observed in a series of patients who underwent single-port RAKAT.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, torsion has been a rare complication for kidneys transplanted into the retroperitoneal space. 32,33 Torsion associated with RAKAT has been accounted for by the intraperitoneal placement of the transplanted kidney, and the argument has been made that the retroperitoneal space should be the preferred location of the transplanted kidney. 17 Lastly, Kaouk et al reported that no postoperative complications were observed in a series of patients who underwent single-port RAKAT.…”
Section: Complicationsmentioning
confidence: 99%
“…A prophylactic nephropexy can be performed to prevent it. However, torsion has been a rare complication for kidneys transplanted into the retroperitoneal space 32,33 . Torsion associated with RAKAT has been accounted for by the intraperitoneal placement of the transplanted kidney, and the argument has been made that the retroperitoneal space should be the preferred location of the transplanted kidney 17 .…”
Section: Complicationsmentioning
confidence: 99%
“…Kidney allograft torsion is a rare complication of kidney transplant that can lead to allograft loss from prolonged ischemia if not quickly corrected with detorsion and nephropexy. This complication has primarily been reported in adult transplant patients who have intraperitoneal placement of the renal allograft in the setting of simultaneous kidney‐pancreas transplantation 1–7 . In pediatric patients, there have been two cases of renal allograft torsion reported, both in patients with prune belly syndrome and intraperitoneal transplants with torsion occurring about 2 months post‐transplant 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…This complication has primarily been reported in adult transplant patients who have intraperitoneal placement of the renal allograft in the setting of simultaneous kidney-pancreas transplantation. [1][2][3][4][5][6][7] In pediatric patients, there have been two cases of renal allograft torsion reported, both in patients with prune belly syndrome and intraperitoneal transplants with torsion occurring about 2 months post-transplant. 8,9 Kidney allografts in appropriately sized patients are preferentially placed retroperitoneally in the right iliac fossa due to the more superficial position of the external iliac vein, which limits mobility of the allograft.…”
mentioning
confidence: 99%